Technical Services for Organizing Crowds, Provided to Pilgrims, During Hajj Season - Choudhry, Abdulaziz Mohammed; Al-Maliki, Mansour Attia; Khurshid, Wissam Walid; Shawli, Yasser Taj (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aims to Identify Technical Services (Expert Systems, Neural Networks, Genetic Algorithms) in Provided to Pilgrims, During Hajj Season, and to measure the impact of Technical Services in Organizing Crowds on developing services Provided to Pilgrims, during Hajj season, the study based on qualitative method depending on questionnaire that was applied on 103 administrative workers in Administration of the affairs of the Grand Mosque in Makkah. The study concluded that there is a high degree of estimation for artificial intelligence in the Administration of the Affairs of the Grand Mosque in Makkah, where it was found through the study that expert systems was in the first rank, followed by genetic algorithms, then neural networks, where all of these dimensions had a high degree of assessment, depending on results the study came up with recommendations the most important of which employing artificial intelligence to organize crowds more in the Administration of the Affairs of the Grand Mosque in Makkah the study shows that the application of artificial intelligence has an important impact on the organization and management of crowds.